2005
DOI: 10.1038/nn1409
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical and asymmetric temporal sensitivity in human auditory cortices

Abstract: Lateralization of function in auditory cortex has remained a persistent puzzle. Previous studies using signals with differing spectrotemporal characteristics support a model in which the left hemisphere is more sensitive to temporal and the right more sensitive to spectral stimulus attributes. Here we use single-trial sparse-acquisition fMRI and a stimulus with parametrically varying segmental structure affecting primarily temporal properties. We show that both left and right auditory cortices are remarkably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
426
6
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 513 publications
(492 citation statements)
references
References 37 publications
57
426
6
3
Order By: Relevance
“…The evidence for a rightward asymmetry of slow integration is growing and the evidence for a leftward asymmetry of rapid integration is unsettled. Minimally, both hemispheres are equipped to deal with subtle temporal variation (Boemio et al 2005). (b) Functional lateralization as a consequence of temporal integration.…”
Section: Multi-time Resolution Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence for a rightward asymmetry of slow integration is growing and the evidence for a leftward asymmetry of rapid integration is unsettled. Minimally, both hemispheres are equipped to deal with subtle temporal variation (Boemio et al 2005). (b) Functional lateralization as a consequence of temporal integration.…”
Section: Multi-time Resolution Processingmentioning
confidence: 99%
“…If distinct auditory cortical fields are found to be differentially sensitive to temporal information, such data would support the model that different time scales are processed in parallel. In a recent fMRI study, Boemio et al (2005) tested this hypothesis using non-speech signals that were constructed to closely match certain properties of speech signals. They observed that STG, bilaterally, is exquisitely sensitive to rapid temporal signals; however, right STS was preferentially driven by longer-duration signals, supporting the hypothesis that signals are not only processed on multiple time scales but also that the processing is partially lateralized, with slower signals differentially associated with right hemisphere mechanisms in higher-order auditory (and the canonical multisensory) area, STS.…”
Section: Multi-time Resolution Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned results challenge this notion and recent models have indeed made use of specifically sized temporal windows of integration for the analysis of speech signals (Poeppel 2003;Poeppel et al 2008), models that heavily rely on neuroimaging evidence (e.g. Boemio et al 2005). In this example, it is clearly the content of a temporal window that matters, not the temporal window itself, i.e.…”
Section: Two-way Non-identity Problemmentioning
confidence: 99%
“…In the general population, speech and language processing are largely lateralized to the left hemisphere, a specialization which is already apparent in infancy (e.g., Dehaene-Lambertz et al 2002). Several studies have linked hemispheric specialization for speech to an asymmetry in cortical auditory tuning and revealed that the auditory cortices are differentially sensitive to particular spectrotemporal features: slow acoustic amplitude modulations (3-7 Hz AM) and spectral aspects, like pitch, are preferentially processed in the right auditory cortex, whereas temporal aspects, like duration, rhythm and faster modulations (12-50 Hz AM), are more left lateralized (e.g., Boemio et al 2005;Jamison et al 2006;Poeppel 2003;Rosen et al 2011;Schönwiesner et al 2005;Zatorre and Belin 2001;Zatorre and Gandour 2008). Given that speech perception requires an accurate tracking of fast temporal cues, e.g., formant transitions (Schwartz and Tallal 1980), it seems natural that speech perception, and by extension linguistic processing, is lateralized to the left hemisphere (Telkemeyer et al 2009; but see Abrams et al 2008).…”
Section: Introductionmentioning
confidence: 99%